Influence of ferric oxide on the crystallization of Li-Zn ferrite anorthite and hematite phases at low temperature ceramic glaze - Supakorn Silakate (2018)
© 2015 Elsevier Ltd. The crystallization mechanism and properties of lithium zinc ferrite (LiZnFe < inf > 2 < /inf > O < inf > 4 < /inf > ) anorthite (CaAl < inf > 2 < /inf > Si < inf > 2 < /inf > O < inf > 8 < /inf > ) and hematite (α-Fe < inf > 2 < /inf > O < inf > 3 < /inf > ) of ceramic glaze containing Li < inf > 2 < /inf > O and ZnO system were studied as a function of Fe < inf > 2 < /inf > O < inf > 3 < /inf > contents. The glaze was fired at 1100°C and the addition of 5-25wt.% Fe < inf > 2 < /inf > O < inf > 3 < /inf > contents developed brown color crystals. A non-isothermal analysis was performed to study the crystallization behavior of LiZnFe < inf > 2 < /inf > O < inf > 4 < /inf > anorthite and hematite using DTA with various heating rates for calculating activation energy and Avrami constant from Kissinger and Augis-Bennett equation. XRD, SEM/EDS and Raman spectroscopy were used to determine the crystalline phases. The occurrence of LiZnFe < inf > 2 < /inf > O < inf > 4 < /inf > anorthite and hematite depended on the Fe < inf > 2 < /inf > O < inf > 3 < /inf > content in the glaze. In the case of 15wt.% Fe < inf > 2 < /inf > O < inf > 3 < /inf > demonstrated the main crystalline phase of LiZnFe < inf > 2 < /inf > O < inf > 4 < /inf > . Furthermore, anorthite and hematite were also found in 25wt.% Fe < inf > 2 < /inf > O < inf > 3 < /inf > content. The values of Avrami constant were 0.9 and 0.5, and the surface crystallization tendency is dominant for these crystalline phases.